Legal Study Of Criminal Acts Of Electricity Theft Reviewed Based On Law No. 30 Of 2009 Concerning Electricity - Rinaldi Kalman; Kusno Kusno; Ahmad Ansyari Siregar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The purpose of this study is to find out and understand the Regulations on Electricity Reviewed Based on Law No. 30 of 2009 Concerning Electricity and Criminal Liability for Perpetrators of Electricity Theft. The type of research used is normative research, with an approach method through legislation. Discussion Results: First, the Regulations on Electricity Reviewed Based on Law No. 30 of 2009 Concerning Electricity are regulated in CHAPTER I to CHAPTER XVII. The Regulations regulate: General Provisions; Principles and Objectives; Control and Business; Management Authority; Utilization of Primary Energy Sources; General Electricity Plan; Electricity Business; Land Use Permits; Selling Prices, Network Rentals, and Electricity Tariffs; Environment and Engineering; Guidance and Supervision; Investigation; Administrative Sanctions; Criminal Provisions, Transitional Provisions; Closing Provisions. Second, Criminal liability for perpetrators of electricity theft is regulated in Article 51 paragraph (3) and Article 53 of Law Number 30 of 2009 concerning Electricity. Article 51 Paragraph (3) which reads